Penyelesaian Sengketa Terhadap Hak Guna Bangunan Atas Tanah Milik Orang Lain - Aprilia, Cindy (UM Purwokerto Press, 2024)
The purpose of writing this article is to explain the issues that often arise in conflicts over building use rights over private property rights. The abstract talks about efforts to resolve disputes. The National Land Agency (BPN) offers non-litigation through mediation services or through other dispute resolution channels. Land ownership is the main issue in the dispute resolution process. Land ownership certificates are a strong source of evidence, but can be revoked if the opposing party has stronger proof of ownership.